Enhancement of ultrasonic-assisted and agitation-assisted flaxseed oil extractions: Kinetic modeling and optimization - Maede Arefizadeh; Danial Behvandi; Shahrokh Shahhosseini; Ahad Ghaemi (Results in Engineering)
The flaxseed oil extraction process has been investigated and enhanced by applying Ultrasonic-Assisted Extraction (UAE), and Mixer-Assisted Extraction (MAE) methods in this study. Response Surface Methodology (RSM) was also utilized to find the optimal values of the extraction parameters. The optimal conditions for UAE were determined to be 42.7 min extraction time, 0.283 mm particle size, and 2.48 W/mL power intensity, achieving the oil yield of 94.56 %. For MAE, the optimal conditions were 54.5 min extraction time, 0.274 mm particle size, 21.1 °C temperature, and 0.74 W/mL agitation intensity, resulting in the oil yield of 96.73 %. RSM showed high reliability with R2 values above 0.99 for both methods. Gas Chromatography Flame Ionization Detector (GC-FID) analysis revealed that UAE and MAE resulted in higher unsaturated fatty acids concentrations (85.8 % and 86 %, respectively) compared to CPE (78.2 %). Kinetic studies indicated that UAE and MAE are more efficient in extracting unsaturated fatty acids, with MAE showing the highest double bond content. The Kinetic models demonstrated that extraction kinetics were controlled primarily by solid-phase resistance, with the washing coefficients being significantly higher than the diffusion coefficients. The Perez model calculated diffusion coefficients of 8.03 × 10⁻12 m2/s for UAE and 1.41 × 10⁻11 m2/s for MAE, activation energies of 16.44 kJ/mol for UAE and 15.64 kJ/mol for MAE.